Adoption of SKPD-03 brought prosperity to the blackgram growers of West Sikkim - Dulal, Jaya Prakash; Subba, Ranjit; Basnett, Dinesh (Indian Farming, 2025)
The adoption of the improved blackgram variety SKPD-03 has led to enhanced productivity and profitability for blackgram growers in West Sikkim, especially in Suldung Kamling and Chakung Chumbung villages. Previously, low yields and limited awareness about high-yielding varieties and crop management practices hindered blackgram production. Through the Cluster Front Line Demonstration (CFLD) program led by Krishi Vigyan Kendra (KVK) under the National Food Security Mission, 60 progressive farmers were introduced to SKPD-03 along with organic practices such as soil application of FYM, vermicompost, and Rhizobium seed treatment. This intervention resulted in an increased yield of `940 kg/ha and a net income of ₹64,000/ha, significantly improving the socio-economic conditions of farmers. The success of SKPD-03 demonstrates the positive impact of high-yielding varieties and integrated crop management on smallholder farmers in Sikkim.